Validation of vacuum extraction protocol for larval sampling of spotted-wing drosophila in blueberries - Babu, Arun; Sial, Ashfaq A. (Frontiers in Agronomy, 2024)
For spotted-wing drosophila, Drosophila suzukii Matsumura, the standard larval sampling protocol from the fruits involves immersing the fruits in hot water, salt, or sugar solution followed by enumerating the larvae that exit from the fruit. In this study, using the fruit samples collected from commercial blueberry farms, we validated the efficacy of a novel D. suzukii larval sampling technique, the vacuum extraction protocol. The larval extraction efficacy of the vacuum extraction method was compared with the salt extraction method using paired fruit samples collected from three different fields for four consecutive weeks. Overall, larval counts detected through the vacuum extraction were significantly higher than those detected through salt extraction in two out of three blueberry fields. Additionally, among the five blueberry fruit sample volumes tested (118, 177, 237, 355, and 473 mL), we identified 355 mL (12 fl. oz.) as the optimum fruit sample volume for vacuum extraction that maximized sampling precision for unit sampling cost. Since D. suzukii larvae exited from fruits after vacuum extraction remain alive and active, a delay in separating the larvae from the sample with coffee filter extraction may result in larval movement back into the fruit flesh. However, compared with immediate processing, delaying coffee filter extraction up to 60 minutes after vacuum incubating the fruit samples at -98 kPa for 60 minutes did not significantly reduce the larval count. Overall, the results of validation trials indicate that vacuum extraction is a promising sampling method for growers to detect D. suzukii larval infestation in blueberries.